Cytotoxicity and mutagenicity of female contraceptives in Allium cepa L. (Research, Society and Development, 2022)
Currently, a large part of the female population uses contraceptive methods due to the benefits provided by this medication. These drugs can be found in oral or injectable form and are basic compounds for progestogen and estrogen. However, despite the benefits, these contraceptives can cause a number of harmful effects as women, due to continuous and prolonged use, in addition to the problem of these compounds being excreted in the sewers, daily, causing problems to the population and the animals exposed. In this context, the present study aimed to evaluate the cytotoxic and mutagenic potential of different contraceptives, using Allium cepa L. as a eukaryotic test system. Four contraceptives were used: indicated for lactating mothers (A1), the following day pill (A2), a drospirenone (A3) and an injectable (A4). Based on the results, conclude what is the A1 contraceptive, which is indicated for women in the lactation phase, shows cytotoxic effect, with a decrease in the mitotic index. However, none of the contraceptives studied were mutagenic for the eukaryotic cells studied. Thus, the data of the present study indicate that chronic studies must be carried out in order to protect humans and other organisms that may be exposed to these substances in the environment.